Effects of low‐frequency intravaginal electrical stimulation on female urinary incontinence, quality of life, and urinary symptoms: A pilot study. Issue 1 (9th October 2019) - Bae, Sangrak; Lee, Kyu Won; Jeong, Hyun Cheol; Park, Bong Hee; Bae, Woong Jin; Lee, Yong Seok; Han, Chang Hee; Kang, Sung Hak; Kim, Sae Woong
Abstract: This study investigated the effects of a low‐frequency home‐based incontinence therapy device on quality of life (QoL) and urinary symptoms in women with urinary incontinence. From May 2017 to February 2018, 34 patients, aged ≥ 20 years, with involuntary urine leakage >2 times/week, were recruited to this study. Patients with severe pelvic organ prolapse, pregnancy, virgin status, and psychological problems were excluded. The incontinence home‐care device treatments were administered in 12‐minute sessions, twice daily for 8 weeks. Simultaneously, hyperthermic conditions of 35°C to 40°C and microvibrations were administered. All patients completed urinary incontinence questionnaires (King's Health Questionnaire [KHQ], Bristol Female Lower Urinary Tract Symptoms [BFLUTS] questionnaire, and the Overactive Bladder Symptom Score [OABSS]) before treatment, as well as 4 and 8 weeks into treatment. Changes in the questionnaire responses over time were compared. Two participants dropped out of the study and there was one screening failure, leaving 31 patients for analysis. After 4 weeks treatment, there were significant improvements in symptoms, such as role limitation, physical limitation, social limitation, personal relationship, emotion, sleep/energy, and severity measures. After 8 weeks treatment, almost all parameters on the KHQ revealed symptomatic improvement. On the BFLUTS, voiding times during activity, nocturia, urgency, urge incontinence, incontinence frequency, stress incontinence, volume leakage, strain to start, intermittency, reduced stream, acute retention, incomplete emptying, and stopping flow showed significant improvements. On the OABSS, almost all storage symptoms improved. Low‐frequency electrical stimulation devices were effective at improving urinary incontinence, which became evident as the duration of treatment increased. Improvement of urgency and frequency was more evident after treatment.